Avetik Isahakyan and Oriental Culture - Kalantaryan, Zhenya (Bulletin of Yerevan University B: Philology, 2025)
The article presents Isahakyan's profound interest in Oriental culture. Already in his native Ghazarapat, Isahakyan had heard the conversations, tales, and songs of the ashughs (folk minstrels), which left a great impact on the young man and contributed to the development of his imagination. On one hand, the romantic impressions received from childhood, and on the other hand, the enthusiasm for the literature of Oriental peoples during his years in Europe, influenced by European philosophers (Nietzsche, Schopenhauer, Kant, and others) and writers (Goethe, Béranger, Dumas...), drive Isahakyan toward the cultivation of Oriental folklore. However, the Orient is a universal concept that encompasses within itself the national amalgamation of different nations and peoples (Indian, Chinese, Persian, Japanese, Egyptian, Hebrew...), their language, religion, and philosophy. In the legends, traditions, and tales belonging to these peoples, Isahakyan emphasizes each people's worldview, customs, and traditions. Isahakyan succeeds in highlighting the mentality and behavior of individual peoples and making visible the enduring significance of wise ideas coming from the ancient world.
Keywords: culture; literature; philosophy; religion; legend; fairy tale; story; Buddhism; Zoroastrianism; worldview